Islamic law and legal system : studies of Saudi Arabia - Vogel, Frank E. (Studies in Islamic law and society, 2000)
This volume offers an examination of the legal system of Saudi Arabia, not only for its own sake but also as a case study for insight into past and present Islamic legal systems.